2016
DOI: 10.1177/1076029615576741
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentrations of Protein Z and Protein Z-Dependent Protease Inhibitor in Patients With Essential Thrombocythemia

Abstract: The pathological consequences of decreased protein Z (PZ) and/or Z-dependent protease inhibitor (ZPI) levels remain as yet unclear, despite a growing body of evidence which supports their involvement in an increased thrombotic risk. The purpose of the present study was 2-fold: to evaluate plasma concentrations of protein Z and ZPI in patients with essential thrombocythemia (ET) and to determine their significance in thrombotic complications. The median (range) plasma concentrations of PZ in our patients with E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…Moreover, all kits used in our study were extensively validated in preceding studies. 10,17,18 For the determination of MPs, MPs-TF, PZ, FX, and total TF, ELISAs by HYPHEN BioMed, SAS (Neuville-sur-Oise, France) were utilized. Microparticles procoagulant activity was determined using a ZYMUPHEN MP-Activity kit and expressed as phosphatidylserine (PS) equivalents (nanomolar PS).…”
Section: Determination Of Coagulation Markersmentioning
confidence: 99%
“…Moreover, all kits used in our study were extensively validated in preceding studies. 10,17,18 For the determination of MPs, MPs-TF, PZ, FX, and total TF, ELISAs by HYPHEN BioMed, SAS (Neuville-sur-Oise, France) were utilized. Microparticles procoagulant activity was determined using a ZYMUPHEN MP-Activity kit and expressed as phosphatidylserine (PS) equivalents (nanomolar PS).…”
Section: Determination Of Coagulation Markersmentioning
confidence: 99%
“…PZ is vitamin K-dependent serum protein and commonly synthesized by vascular endothelial cells [17] . Its structure is similar to other K-dependent factors, such as VII, IX, and protein C [18] . Previous studies showed that PZ can acts an anticoagulant, like protein C and protein S. ZPI is a member of serpin superfamily and could rapidly inhibit activation of factor Xa with the requirement of PZ, calcium, and perocoagulant phospholipids, or suppress the activation of factor XI in the absence of the aforementioned cofactors [19] .…”
Section: Discussionmentioning
confidence: 77%
“…PZ is a kind of vitamin K-dependent serum protein and commonly synthesized by vascular endothelial cells [17]. Its structure is similar to other Kdependent factors, such as VII, IX, and protein C [18]. ZPI is a member of serpin superfamily, which can rapidly inhibit activation of factor Xa when having PZ, calcium and procoagulant membranes.…”
Section: Discussionmentioning
confidence: 99%